An Italian Disease-Based Registry of Axial and Peripheral Spondyloarthritis: The SIRENA Study - Zabotti, Alen; Luchetti, Michele Maria; Selmi, Carlo Francesco; Ramonda, Roberta; Grembiale, Rosa Daniela; Dagna, Lorenzo; D'Angelo, Salvatore; Cafaro, Giacomo; De Vita, Salvatore; Felicetti, Mara; Marelli, Silvia; Frigerio, Daniela; et al. (Frontiers in Medicine, 2021)
Introduction: Data on the clinical presentation and management of early and mild Spondyloarthritis (SpA) are limited. Objectives: To describe the baseline characteristics of disease-modifying antirheumatic drugs (DMARDs)-naive patients with axial and peripheral SpA. Methods: SIRENA is an ongoing, Italian, multicenter, prospective registry of patients with a first or newly confirmed diagnosis of SpA according to ASAS criteria, and naïve to conventional, targeted and biological DMARDs. Patients were enrolled between June 2017 and June 2019 and classified into groups presenting with either predominantly axial or peripheral manifestations; they are being followed for 2 years, with evaluation every 6 months according to clinical practice. Differences in baseline demographic, lifestyle and clinical characteristics between axial and peripheral SpA were evaluated. Results: 350 patients were enrolled: 123 (35.1%) axial and 227 (64.9%) peripheral patients. Axial SpA patients were significantly younger at enrollment (median age: 44 versus 53 years), had significantly more anxiety/depression (13% versus 2.6%), and expressed a higher disease activity compared to peripheral SpA patients. Peripheral SpA patients had significantly more cardiometabolic disorders (33.0% versus 18.7%), skin psoriasis (65.2% versus 21.1%) and nail psoriasis (35.5% versus 17.1%) than axial ones. Dactylitis, enthesitis and fibromyalgia were observed, respectively, in 17.6%, 51.2% and 5.7% of axial SpA patients and in 24.3%, 40.0% and 3.1% of peripheral SpA patients. In both disease groups, women tended to report depression, joint tenderness, and higher disease activity more frequently than their male counterparts. At inclusion, a new diagnosis of SpA was performed in 58% of axial and 77% of peripheral patients, with a median time from symptom onset to diagnosis of 36 months and 24 months, respectively. At baseline, most axial SpA patients (77%) started a biological DMARD and over half of peripheral patients started a conventional DMARD. Conclusions: Based on a well-characterized clinical registry of SpA, we provided real-world insights on the clinical features of DMARDs-naive SpA patients, pointing out major differences between axial and peripheral disease in terms of clinical characteristics and treatment pattern. Future prospective evaluations within the SIRENA study will improve knowledge on SpA and contribute to defining the best therapeutic approach.